Nurses' recruitment and selection: Lessons learned from the COVID-19 pandemic in Indonesia - Nazliansyah Nazliansyah; Joko Gunawan (Belitung Raya Foundation, 2022)
The purpose of this paper is to describe the current state of the recruitment and selection of nurses in Indonesia as a reflection on the pandemic. This article may be useful for evaluating the effectiveness of the human resource management system in Indonesia.  However, nurses are heroes to be appreciated.